Nurse/Midwives' practices during labor and delivery in Maternity Teaching Hospital in Erbil City - Lana Abdul-Hamed Muhammad Nuriy; Hamdia Mirkhan Ahmed (Hawler Medical University, 2018)
Background and objective: Labor is a life-changing event and is a high-risk time for both the fetus and the mother which affects them physically and emotionally, so proper care during labor and delivery is important. The study assessed the quality of the labor and delivery care by nurse/midwives. Methods: A study was carried out to observe nurse/midwives' practices during the stages of labor and delivery. The study was conducted in the delivery room of the Maternity Teaching Hospital in Erbil City, during the period 28th February 2013 to 20th May 2013. The non-probability sample included 15 midwives who gave care to mothers during labor. Data were collected through a questionnaire format and observation checklist. Results: Midwives did not perform the following practice during labor and delivery: pre-paring the mother (84%), checking vital signs (93.3%), using aseptic technique for fixing a cannula (96.6%), providing privacy for the mother (84%), and using sterile technique for vaginal examination, catheterization, and episiotomy (91.6%) (91.7%) (92.5%) respectively, monitoring uterine contraction (98.3%), checking the progress of labor (93.4%) and se-lecting a suitable position for delivery (93%). Conclusion: Nurse/midwives did not provide proper care during labor and delivery. Improvements in their practice through training courses and changing hospital and delivery room policies is recommended.